In vitro antibacterial properties of etlingera elatior flower extracts against acne-inducing bacteria - Nurul Saidah Din
Acne is one of the most commonly encountered dermatological problems and affects approximately 80% of adolescents. Multiple factors are associated with the pathogenesis of acne and bacterial colonisation has been identified as one of the causative factors involved. Propionibacterium acnes and Staphylococcus aureus are known to be among the main pathogens of acne. Treatment with currently available antibacterial agents may lead to unfavourable side-effects and the emergence of resistant strains. Etlingera elatior flower or 'bunga kantan' is a well-known medicinal plant in Malaysia with various pharmaceutical properties including antibacterial. however, the antibacterial properties of E. elatior flower extracts against these bacteria are inadequately reported. Thus, this study aimed to investigate the antibacterial properties of the flower extracts against the two acne-inducing bacteria, P. acnes and S. aureus, E. elatior flowers extracts were obtained using three solvents with different polarities known as n-hexane (non-polar), dichloromethane (semi-polar) and ethanol (polar). Their antibacterial properties were evaluated by disk diffusion and broth dilution assays by determining the inhibition zone diameter, Minimum Inhibitory Concentration (MIC) and Minimum Bacterial Concentration (MBC). Total Phenolic Acid (TPC) and Total Flavonoid Content (TFC) were estimed using Folin-Ciocalteu and aluminium chloride colorimetric assay respectively. Morphological changes of the treated bacteria were studied using a scanning electron microscope (SEM). All of the extracts were found to have antibacterial properties against the bacteria. The dichloromethane E. elatior flowers extract showed the highest antibacterial properties against P. acnes whereby at the concentrarion of 25 mg/mL, it has demonstrated the widest inhibition zone (11.39±0.45 mm) and the lowest MIC (6.25 mg/mL) and MBC (12.5 mg/mL). The ethanolic extract of the flowers has shown the highest antibacterial properties againsts S. aureus whereby at the concentration of 50 mg/mL, the inhibition zone was 6.21 ± 0.25 mm and the MIC and MBC were both 12.5 mm/mL. The ethanolic E. elatior flowers extract also demonstrated the highest phenolic acid and flavonoid contents; 966.304 ± 114.08 mg GAE/g and 796.33 ± 65.78 mg QE/g, respectively. This was followed by the dichloromethane and n-hexane E. elatior flowers extracts. Significant morphological changes of the treated bacteria were observed. This result suggests the E. elatior flowers extracts exhibited antibacterial properties against P. acnes and S. aureus and could potentially be used as an alternative treatment against acne.